Nikah dalam Lamaran Orang - Maulana Alghifari Harahap; Faiz Nayla Chasnun (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Bondage status is the position of an individual which is determined based on relationships with other individuals in society who provide goods or a sum of money to be used as a bond at the proposal event so that no one can take the woman who has been proposed to. A sermon is a request from a man to a woman to become his wife, in ways that generally apply in society. This research aims to explain the definition of khitbah, its requirements, the views of the ulama, including the opinions of Jumhur and Imam Malik, as well as the causes of differences of opinion among the ulama. It was found that the sermon is a recommendation of Islamic law which provides space for prospective partners to get to know and understand each other. Some ulama view khitbah as sunnah, while the prohibition on applying for someone else's proposal is considered haram according to the majority of ulama, with certain exceptions. This study concludes the importance of maintaining ethics in sermons to create a harmonious marital relationship, in accordance with Islamic values.